PANDANGAN MAHASISWA OUTBOUND UNIVERSITAS HKBP NOMMENSEN MEDAN TERHADAP KEGIATAN PERTUKARAN MAHASISWA MERDEKA - Sitorus, Parlindungan; Sinaga, Gresia Ledy; Zega, Emanuel; Sinaga, Fajar Gohanda (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nommensen, 2023)
This article aims to find out students' views on the activities of the independent student exchange program, and find out students' understanding of student exchanges and what are the obstacles and obstacles experienced by students when participating in student exchange activities. This research uses the case study method, with a focus on the implementation of learning activities off campus, namely student exchanges organized by several study programs, HKBP Nommensen University. Observations were made on 20 students consisting of several study programs in carrying out a student exchange program at HKBP Nommensen university. Data analysis uses data from observations through questionnaires sent via Google form to students. The results of this study indicate that students have a positive view of the implementation of the student exchange program at HKBP Nommensen University and even students want to recommend this activity to others because this activity is very useful. There are several obstacles faced by students at the stages of registration, selection, announcement and implementation. The constraints experienced were the completeness of the files, the difficulty of using the application, the courses at the destination university were not in accordance with the semester courses that were taking place at the original university, and it was difficult to adapt to the new environment.